Cucumber-Peanut Intercropping: The Effects on Vegetative Growth and Yield Productivity - Mardhiana; Eko Hary Pudjiwati; Nurul Chairiyah; Junarius bin Yakobus; Muh. Adiwena (Jurnal Penelitian Pendidikan IPA, 2026)
Intercropping is acknowledged as an effective agricultural intensification strategy for limited land. Planting time is an important factor in intercropping systems because it may intensify canopy overlap and shading, particularly because both crops rely on the C3 photosynthetic pathway, potentially reducing growth and yield. This study examined the effect of different planting times for cucumber (Cucumis sativus L.) and peanut (Arachis hypogaea L.). The study was conducted from October 2023 to February 2024 with a one-factor randomized block design. Five treatments were applied: simultaneous planting and cucumber planting at 1, 2, 3, and 4 weeks after peanuts, each replicated five times. Several data were analyzed using analysis of variance (F-test), followed by Tukey’s HSD test at the 5% significance level. This study confirms that differences in planting time between cucumbers and peanuts significantly affect soil macronutrient dynamics, growth and production, and land use efficiency. Soil macronutrient analysis showed that simultaneous planting (P1) resulted the highest soil nitrogen increase (0.38%). However, this treatment also caused a reduction in phosphorus to 15.15 mg per 100 g of soil and potassium to 13.48 mg per 100 g of soil. In contrast, excessive delay (P5) caused nitrogen to drop to 0.11% and phosphorus to decline to 14.19 mg per 100 g soil, despite potassium remaining relatively high (17.87 mg per 100 g of soil). Simultaneous planting produced the highest vegetative growth of cucumber, with an average of 40.68 leaves per plant, the greatest fruit length (22.16 cm), individual fruit weight (414.55 g), and total fruit weight per plant (2498.39 g). Delaying cucumber planting resulted in the lowest value of 828.45 g in P5. The highest pod weight was recorded in P1 at 62.46 g per plant. In contrast, planting cucumbers one week after peanuts (P2) resulted in the lowest peanut yield, at only 47.14 g per plant. All treatments achieved LER values greater than 1, confirming the superiority of intercropping over monoculture. The highest LER was obtained in P1 (1.61). In conclusion, simultaneous planting of cucumbers and peanuts provides the most optimal balance between soil nutrient utilization, crop growth, yield, and land use efficiency. Therefore, synchronized planting time is a key management strategy for improving productivity and sustainability in cucumber–peanut intercropping systems under limited land conditions.